Final Report on Ganges Coordination and Change Enabling Project (G5) - BRAC (2014)
The Coordination and Change Enabling Project (G5) worked in providing an enabling environment that promote connectivity of project research across topics and scales, from household agriculture- aquaculture farming systems to community polder water management through broader land use planning. The project also served as an interface between the programme and a variety of existing and potential stakeholders and worked towards scaling out research results to multiple stakeholders with common interest in achieving the goals for the CPWF for the Ganges coastal zone. Another important feature of this project is to increase the farm household income and productivity through collaboration with CSISA-BD project principally focusing on improved cereal cropping systems including fish and use of improved varieties and crop management technologies as well.